Arquivologia e administração: uma análise da produção científica com foco na interdisciplinaridade - Santos, Talitha Ribeiro dos (Brasil, 2024)
Archival science has interacted with other sciences since its emergence, but establishing the type of relationship that exists is still a complex task today. The present research aims to present the interdisciplinary relationships between Archival Science and Administration through the analysis of scientific production with a focus on interdisciplinarity. As we understood the main concepts of Archiving, Administration and Interdisciplinarity, three searches were carried out using these keywords in the Information Science Database (Brapci). For each result sought, a spreadsheet was created in Exel so that we could identify the most productive themes, journals, types of authorship and authors. When searching only for the keyword interdisciplinarity, 576 articles were retrieved, of which 150 presented interdisciplinary relationships between Archival Science and other sciences. In this way, by structuring and studying the data from each article in spreadsheets, it was possible to verify the level of interdisciplinarity existing in scientific productions. The research points out that, even though there is no consensus among authors on the concept and applicability of interdisciplinarity, research on this topic is quite significant. This suggests that within the academic research environment there is a certain degree of interdisciplinary relationship between sciences.